Incorporating coronary calcification by computed tomography into CHA2DS2-VASc score: impact on cardiovascular outcomes in patients with atrial fibrillation. Issue 8 (15th February 2021) - Wang, Tom Kai Ming; Chan, Nicholas; Cremer, Paul C; Kanj, Mohamed; Baranowski, Bryan; Saliba, Walid; Wazni, Oussama M; Jaber, Wael A
Abstract: Aims: CHA2 DS2 -VASc score is widely utilized for risk stratification and guiding anticoagulation in patients with atrial fibrillation (AF). Cardiac computed tomography (CCT) routinely performed for pulmonary vein isolation (PVI) can also identify coronary artery calcifications (CAC). We evaluated the frequency and outcomes of incorporating CAC into the CHA2 DS2 -VASc score in AF patients undergoing PVI. Methods and results: Consecutive patients in a prospective PVI registry during 2014–18 having CCT within 1 year of PVI were studied. Reclassification of CHA2 DS2 -VASc score and associations between CAC as a binary variable detected on CCT with clinical characteristics, stroke as primary endpoint, death, myocardial infarction, and major adverse cardiovascular events (MACE) were analysed. Amongst 3604 AF patients, 2238 (62.1%) had CAC detected on CCT and was associated with most traditional cardiovascular risk factors. Coronary artery calcification was independently associated with all pre-specified endpoints adjusting for clinical parameters in multivariable analysis. Adjusting for CHA2 DS2 -VASc score, CAC was associated with stroke (hazards ratio 3.64, 95% confidence interval 1.25–10.6, P = 0.018), death (2.26, 1.29–3.98, P = 0.006), and MACE (2.08, 1.36–3.16, P = 0.001) during 2.8 ± 1.6-year follow-up. Incorporating CAC as a vascular disease parameter of CHA2 DS2 -VASc score, anticoagulation decision-making would be revised in 723 (20.1%) patients, including an additional 488 (13.5%) patients where anticoagulation would be now indicated. Conclusion: Coronary artery calcification is prevalent in AF patients undergoing PVI and independently associated stroke, death and MACE even when adjusted for traditional CHA2 DS2 -VASc score. Adding CAC as vascular component to the CHA2 DS2 -VASc score requires further research as it potentially modified the anticoagulation management in 20% of our AF cohort.